Consumption of branched-chain amino acids is inversely associated with central obesity and cardiometabolic features in a population of Brazilian middle-aged men: Potential role of leucine intake - Cocate, P. G.; Natali, A. J.; Oliveira, A. de; Alfenas, R. C.; Hermsdorff, H. H. M. (The journal of nutrition, health & aging, 2014)
To assess the potential associations of branched-chain amino acids (BCAA) consumption with central obesity (CObesity) and cardiometabolic risk factors in a population of Brazilian middle-aged men. Special attention was given to leucine intake. Cross-sectional study. Universidade Federal de Viçosa, Viçosa, Brazil. Two-hundred ninety-six middle-aged men (Age: 50.5 ± 5.0 years; Body mass index: 25.8 ± 3.5 kg/m2). Anthropometry, lifestyle features, blood biochemical parameters were assessed and dietary intake was estimated by a food frequency questionnaire. Participants were classified by the occurrence of CObesity, hypertriglyceridemia (HTG), hypertriglyceridemic waist phenotype (HWP) and metabolic syndrome (MetS). Subjects in the BCAA highest tertile (≥0.17 g/kg/d) presented lower occurrence of CObesity (36.0% vs 72.4%, P<0.01, z=−5.10), HTG (17.0% vs 30.6% P<0.032, z=−2.32), HWP (23.0% vs 46.9%, P<0.01, z=−3.57) and MetS (19.0% vs 34.7%, P<0.01, z=−2.57). They also exhibited lower values for Castelli index (total cholesterol:HDL-c) and triglycerides: HDL-c ratio than those in the first tertile, regardless of interfering factors (i.e. habitual physical activity, work position, smoking habit, and energy intake). Interestingly, leucine consumption showed similar associations with cardiometabolic risk factors, as compared to BCAA consumption (P<0.05). BCAA consumption was cross-sectionally and negatively associated with relevant cardiometabolic risk factors in a population of Brazilian middle-aged men. The content of leucine in BCAA consumption may have contributed to such relationship.
Keywords: Amino acids; Central obesity; Metabolic syndrome; Cardiometabolic risk factors